(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The purpose of this study was to characterize the mitochondrial COX-1 gene of Sarcoptes scabiei in rabbits from three districts of Malang, Nganjuk, and Kediri, East Java, Indonesia. The gene was aligned with a DNA isolated from S. scabiei of Chong’qing rabbit (accession number: EU256388.1) to construct a molecular analysis of phylogenetic in S. scabiei COX-1 gene. Materials and Methods: This study has been verified by the Committee Ethics (Faculty of Veterinary Medicine, Universitas Airlangga). The mites were collected and identified from rabbits that have an indication of scabies infection. DNA was extracted with QIAamp DNA mini kit and polymerase chain reaction (PCR) analysis was done. The PCR products were purified with the protocol of the BigDye XTerminator™ Purification Kit (Thermo Scientific) and were double-sequenced with the forward and reverse PCR primers of ABI PRISM 310 Genetic Analyzer. The sequence product was confirmed with Clone Manager Professional 9 (Sci-Ed Software) and the Neighbor-Joining method was done with MEGA6 to build a phylogenetic tree. Results: The target product of DNA amplification in this PCR was around 290-bp. The amplicon was visualized in 2% of agarose gel electrophoresis. The homology analysis of these sequences showed that it had more than 99% similarity. Conclusion: COX-1 gene sequences of S. scabiei from rabbits in Malang, Nganjuk, and Kediri were very similar to COX-1 gene sequences in S. scabiei acquired from several hosts according to NCBI data. J. Adv. Vet. Anim. Res., 6(4): 445-450, December 2019